The redox titration of Fe (II) ions with K2Cr2O7 using a potentiometry method the effect of EDTA and SCN- ligands - Herlina, Herlina; Razali, Muhammad (Pharmaciana, 2024)
Complexometric titration is often used for determining the metal content, either through direct titration or back titration. This study aimed to investigate redox titration between Mohr salt solutions and potassium dichromate in an acidic atmosphere in the pH range 2. The results showed that the reaction proceeded effectively at pH 2, with Mohr's salt solution acting as titrant. Furthermore, experiments were conducted to compare the effectiveness of EDTA ligands and SCN- ligands in improving the sharpness of the Fe2+/ Cr2O72- redox titration curve at pH 2. Results show that EDTA ligands are more effective than SCN- ligands in improving the sharpness of the titration curve. However, it should be noted that the addition of EDTA ligands can shift the equivalent point volume earlier, so adjustments need to be made in redox titration analysis. Research has also shown that adding excess moles of EDTA to total Fe (II) ions can decrease redox potential in Fe2+/ Cr2O72- systems. These results provide additional insight into the use of EDTA ligands in redox titration analysis and their relevance to redox potential changes in the systems studied.